La conservation des ossements fossiles : le cas des Iguanodons de Bernissart - Pascal Godefroit; Thierry Leduc (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The discovery, in 1878, of more than twenty complete skeletons of Iguanodons at Bernissart (Belgium) is a major event in the history of palaeontology. These 125 million years old skeletons were extremely weakened because of the great amont of pyrite inside the bones. The extraction and restoration of these fossils therefore necessitated, at the end of the 19th Century, boundless ingenuity. Their preservation still requires a constant monitoring and recurrent appropriate treatments.